2020
DOI: 10.3390/ijms21217844
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-Independent and Wnt-Dependent Effects of APC Loss on the Chemotherapeutic Response

Abstract: Resistance to chemotherapy occurs through mechanisms within the epithelial tumor cells or through interactions with components of the tumor microenvironment (TME). Chemoresistance and the development of recurrent tumors are two of the leading factors of cancer-related deaths. The Adenomatous Polyposis Coli (APC) tumor suppressor is lost in many different cancers, including colorectal, breast, and prostate cancer, and its loss correlates with a decreased overall survival in cancer patients. While APC is commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 109 publications
0
18
0
Order By: Relevance
“…Furthermore, APC mutations have been shown to induce chemoresistance through angiogenesis by interacting with the tumour microenvironment. This is supportive of a connection between APC mutation status and MMC resistance, considering that MMC works through reduction that is inhibited by oxygen and hence blood supply [17] , [18] . Lastly, in vivo studies showed that loss of APC was associated with chemoresistance through alterations of the immune cell infiltration [17] .…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, APC mutations have been shown to induce chemoresistance through angiogenesis by interacting with the tumour microenvironment. This is supportive of a connection between APC mutation status and MMC resistance, considering that MMC works through reduction that is inhibited by oxygen and hence blood supply [17] , [18] . Lastly, in vivo studies showed that loss of APC was associated with chemoresistance through alterations of the immune cell infiltration [17] .…”
Section: Discussionmentioning
confidence: 55%
“…MiR-BART19-3p is implicated in the activation of Wnt signaling pathway by targeting tumor suppressor APC, enhancing proliferation and suppressing apoptosis of EBV-infected tumor cells [ 21 ]. APC can downregulate Wnt signaling pathway by reducing the accumulation of β-catenin in the nucleus, thereby inhibit tumor growth and chemoresistance in multiple cancer types [ 34 , 35 ]. Here in EBV-positive B-lymphoma cells, circEAF2 specifically targeted miR-BART19-3p, upregulated APC, and suppressed downstream β-catenin, indicative a viral miRNA-mediated mechanism underlying EBV + DLBCL progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiological mechanisms that drive colorectal carcinogenesis are heterogeneous, the tumoral transformation of normal intestinal epithelial cells (IEC) depends on an event that triggers chromosomal instability (CIN) and the accumulation of somatic mutations and epigenetic alterations [ 20 , 61 , 62 ]. In this context, the deregulation of the Wnt/β-catenin signaling components is the most frequent event and leads to hyperproliferation in the intestinal crypt [ 63 , 64 ].…”
Section: The Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%